Anthropogenic N deposition increases soil organic matter accumulation without altering its biochemical composition. (11th October 2016) - Zak, Donald R.; Freedman, Zachary B.; Upchurch, Rima A.; Steffens, Markus; Kögel‐Knabner, Ingrid
Abstract: Accumulating evidence indicates that future rates of atmospheric N deposition have the potential to increase soil C storage by reducing the decay of plant litter and soil organic matter (SOM). Although the microbial mechanism underlying this response is not well understood, a decline in decay could alter the amount, as well as biochemical composition of SOM. Here, we used size‐density fractionation and solid‐state 13 C‐NMR spectroscopy to explore the extent to which declines in microbial decay in a long‐term ( ca . 20 yrs.) N deposition experiment have altered the biochemical composition of forest floor, bulk mineral soil, as well as free and occluded particulate organic matter. Significant amounts of organic matter have accumulated in occluded particulate organic matter (~20%; oPOM); however, experimental N deposition had not altered the abundance of carboxyl, aryl, alkyl, or O/N‐alkyl C in forest floor, bulk mineral soil, or any soil fraction. These observations suggest that biochemically equivalent organic matter has accumulated in oPOM at a greater rate under experimental N deposition, relative to the ambient treatment. Although we do not understand the process by which experimental N deposition has fostered the occlusion of organic matter by mineral soil particles, our results highlight the importance of interactions among the products of microbial decay and the chemical and physical properties of silt and clay particles that occlude organic matter from microbial attack. Because oPOM can reside in soils for decades to centuries, organic matter accumulating under future rates of anthropogenic N deposition could remain in soil for long periods of time. If temperate forest soils in the Northern Hemisphere respond like those in our experiment, then unabated deposition of anthropogenic N from the atmosphere has the potential to foster greater soil C storage, especially in fine‐texture forest soils.